1997
DOI: 10.1021/jf960778x
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of Chloramben on a Soil Surface:  A Laboratory-Controlled Study

Abstract: Photodegradation of chloramben was conducted on a silt-loam soil under xenon irradiance using a laboratory soil photolysis apparatus. The study was conducted using three sets of soil conditions:  active moist soil, sterilized moist soil, and dry (air-dry) soil, with temperature-controlled constantly at 25 ± 1 °C. Of all three soil conditions, application of chloramben on active moist soil, where moisture was maintained at approximately 75% field moisture capacity (FMC) at 0.33 bar, generated the most accelerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…This is a reasonable penetration depth for the chemical upon application, allows for direct photolysis to be fully effective, and permits the investigation of mobility of the pesticide through the soil. Similar results have been obtained using the herbicide chloramben (17).…”
Section: Light Transmittance In Relation To Soil Depthsupporting
confidence: 86%
“…This is a reasonable penetration depth for the chemical upon application, allows for direct photolysis to be fully effective, and permits the investigation of mobility of the pesticide through the soil. Similar results have been obtained using the herbicide chloramben (17).…”
Section: Light Transmittance In Relation To Soil Depthsupporting
confidence: 86%
“…After the 1-min incubation period, the assay mixtures in the S, B, R HCl-1 mM and R HCl-0 mM tubes are mixed with 10 ml 1 M Tris by brief vortexing (to adjust the assay mixture pH to [7][8], centrifuged at 12,000g for 1 min and the resulting supernatants are collected for fluorescence measurement.…”
Section: Notes: I To Verify That the Net Fu 2-oh-e þ Corresponds To mentioning
confidence: 99%
“…Studies on the photochemical oxidation of xenobiotic organic carbon (herbicides, insecticides and pesticides) in agricultural soils suggested that 1 O 2 generated by sunlight via the photosensitization of soil organics (and possibly of Ti-and Zn-oxides) to be the main oxidant 5 . The involvement of other reactive oxygen species (ROSs) such as superoxide (O 2 Á À ) and hydroxy ( Á OH) radical has been hypothesized as well [6][7][8][9][10][11] . OH is postulated to result indirectly from the reaction of water with humic substances in the excited triplet state or from degradation of H 2 O 2 by transition metal (Me tr ) cations such as Fe 3 þ via a photo-Fenton reaction 10 .…”
mentioning
confidence: 99%
“…The chamber was connected with an air-conditioning unit to obtain the desired temperature, humidity, and flow rate of air that passes over the plants into volatile traps, and the ceiling of the chamber was made of a special glass transmittimg light from a metal-halogenide lamp to simulate exposure to natural sunlight. 10, based on the literature (Klehr et al 1983;Katagi 1990;Misra et al 1997;Kromer et al 1999;Balmer et al 2000). However, these apparati are not readily available and their maintenance is difficult; therefore, photodegradation of pesticides on plants has been mostly examined with metabolism studies.…”
Section: B Photolysis Chambersmentioning
confidence: 99%